Investigating archaeological cultures material culture, variability, and transmission - Roberts, Benjamin W.; Vander Linden, Marc (Springer New York, 2011)
Since the early 20th century, archaeologists across the world have defined archaeological cultures based on distinct similarities in burials, settlements, technology or objects in space and time. Archaeology has thus many accepted definitions of 'archaeological cultures' but these have all come into question. Yet, archaeological cultures remain the framework for global prehistory. This volume brings together 17 international case-studies exploring archaeological cultures for regions around the globe and from the Paleolithic to the Bronze Age and beyond. Taking lessons and overarching themes from these studies, the contributors draw important conclusions about cultural transmission, technological innovation, and cultural development. The result is a comprehensive approach to 'archaeological cultures' addressing specific regions throughout Asia, Europe, North and South America and Africa. This work will be valuable to all archaeologists and cultural anthropologists, particularly those studying material culture. - Publisher's description.